Implementation and Operational Research: High Loss to Follow-up Among Children on Pre-ART Care Under National AIDS Program in Madurai, South India. (1st July 2015) - Ganga Devi, N. Poorana; Ajay, Kumar M. V.; Palanivel, C.; Sahu, Swaroop; Selvaraj, M.; Valan, AS.; Rewari, BB.; Soumya, S.
Abstract : Background: Information on the follow-up of HIV-infected children enrolled into preantiretroviral therapy (Pre-ART) care under routine program settings is limited in India. Knowledge on the magnitude of loss to follow-up (LFU) and its reasons will help programs to retain children in HIV care. We aimed to assess the proportion of LFU among children in Pre-ART care and its associated factors. Methods: In this retrospective cohort study, we reviewed the records of all HIV-infected children (aged <15 years) registered from 2005 to 2012 at an ART center, Madurai, South India. LFU during Pre-ART care was defined as having not visited the ART center within a year of registration. Results: Of 426 children enrolled in Pre-ART care, 211 (49%) were females and 301 (71%) were in the 5- to 14-year age group. At 1 year of registration, 348 (82%) were lost to follow-up. Of 348, 81 returned to care after 1 year of enrollment, whereas 267 (63% of all children) were permanently lost to follow-up. The proportion of LFU remained high from 2005 to 2012. WHO staging, CD4 count, and opportunistic infection were the significant factors associated with lost to follow-up on multivariate analysis. Conclusions: LFU was alarmingly high indicating poor clinical and programmatic monitoring among HIV-infected children enrolled in Pre-ART care. A system for active tracing of those missing a clinic appointment intensified supervision, and monitoring along with qualitative research is urgently needed. This will help to understand the exact reasons for LFU based on which effective interventions may be planned for reducing such losses.